1996
DOI: 10.1111/j.1440-1754.1996.tb00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Visits to medical practitioners in the first 6 months of life

Abstract: A previously undocumented level of postnatal use of medical practitioner services is presented. It suggests a significant level of postnatal maternal and infant morbidity that requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…At 6-9 months the most common problems reported were hearing concerns, visual concerns and abnormal hip examinations. An Australian study in 1996 55 reported that 57% of consultations with medical practitioners in the first 6 months of life were for the babies; mothers' consultations accounted for 43%. This is similar to our findings.…”
Section: Discussion and Conclusion On Referralsmentioning
confidence: 99%
“…At 6-9 months the most common problems reported were hearing concerns, visual concerns and abnormal hip examinations. An Australian study in 1996 55 reported that 57% of consultations with medical practitioners in the first 6 months of life were for the babies; mothers' consultations accounted for 43%. This is similar to our findings.…”
Section: Discussion and Conclusion On Referralsmentioning
confidence: 99%
“…Analysis of the Health Insurance Commission data for a random sample of recent mothers in Victoria showed that the mean number of visits to GPs by a mother/baby dyad in the six months following birth was 7.7 [24]. Similarly, in a large Victorian survey over 92% of GPs described themselves as involved in postnatal care, but neither the common physical health problems described above, nor depression, were issues which GPs considered part of routine postnatal care, and more tellingly, both were areas where the GPs rated themselves as not very confident [25].…”
Section: Introductionmentioning
confidence: 99%
“…Gunn et al . used aggregated Medicare data to examine the use of GPs services by mothers and babies in the 6 months post‐partum with a sample of Victorian babies born in 1993 . They found that mothers and infants made an average of 3.5 visits and 4.2 visits to a GP, respectively.…”
mentioning
confidence: 99%
“…Published studies that report on a wider range of HS used by mothers and babies, as well as on factors associated with use in the first 6 months post‐partum, are scarce . In Melbourne, Australia, Goldfeld et al .…”
mentioning
confidence: 99%